Optical properties and laser performance of Ho : LuAG ceramics - Yang, Hao (2014)
Lutetium aluminum garnet (LuAG) is a garnet isostructure similar to yttrium aluminum garnet (YAG). High optical quality of 1.0 mol% Ho3+ doped LuAG transparent polycrystalline ceramics were fabricated successfully by reactive sintering method. The microstructures, optical properties and laser performance of the Ho:LuAG ceramics were investigated in this study. The in-line transmittance of Ho:LuAG transparent ceramics is higher than 84% at 2500 nm. The absorption coefficient of 1.0 mol% Ho:LuAG is 0.88 cm–1 at 1906 nm and its absorption cross section is calculated to be 0.62×10–20 cm2. The laser oscillation of Ho:LuAG transparent ceramic without coated was also firstly obtained in this study.